Math 4470/5470 Partial Differential Equations Prof. Carlson Homework 9 Text section 5.1 2. Let φ(x) = x2 for 0 ≤ x ≤ 1. a) Calculate the Fourier sine series. Solution Since l = 1 the Fourier sine series is ∞ X Am sin(mπx), m=1 where the Fourier coefficients are Z 1 x2 sin(mπx) dx. Am = 2 0 Integration by parts gives 1 (cos mπx) dx mπ mπ 0 0 Z 1 (sin mπx) (− cos mπ) (sin mπx) 1 dx =2 + 4x −4 2 mπ (mπ) (mπ)2 0 0 (−1)m+1 (−1)m+1 (cos mπx) 1 (−1)m − 1 =2 +4 +4 . =2 mπ (mπ)3 0 mπ (mπ)3 2 (− cos mπx) Z 1 +4 Am = 2x x b) Calculate the Fourier cosine series. Solution The Fourier cosine series series is ∞ X A0 + Am cos(mπx), 2 m=1 where the Fourier coefficients are Z 1 x2 cos(mπx) dx. Am = 2 0 For m 6= 0 integration by parts gives Am Z 1 1 (sin mπx) (sin mπx) x = 2x2 dx −4 mπ mπ 0 0 1 Z 1 (cos mπx) (−1)m (cos mπx) 1 dx = 4 . = 4x −4 (mπ)2 0 (mπ)2 (mπ)2 0 We also have A0 = 2/3. 5. Given the Fourier sine series of φ(x) = x on (0, l), assume that the series can be integrated term by term, a fact that will be shown later. a) Find the Fourier cosine series for x2 /2. Find the constant of integration. Solution From p. 109 we have x= ∞ X (−1)m+1 m=1 2l sin(mπx/l). mπ Integration of both sides gives Z x ∞ X 2l2 cos(mπx/l). t dt = x /2 = C + (−1) 2 π2 m m=1 2 m The constant of integration is the missing coefficient A0 1 C= = 2 l l Z 0 x2 dx = l2 /6. 2 b) By setting x = 0, find the sum ∞ X (−1)n+1 . 2 n n=1 Solution Setting x = 0 gives ∞ X 2l2 0 = l /6 + (−1) , 2 π2 m m=1 2 or 2 π /12 = ∞ X m (−1)m+1 m=1 2 1 . m2 8. A rod has length l = 1 and constant k = 1. Its temperature satisfies the heat equation with boundary conditions u(t, 0) = 0, u(t, 1) = 1. The initial temperature is φ(x) = n 5x/2, 3 − 2x, 0 < x < 2/3, 2/3 < x < 1. o Find the solution, including the coefficients. Solution The equilibrium solution is U = x. We consider v(t, x) = u(t, x) − x. The function v satisfies the heat equation and boundary conditions vt = vxx , v(0) = 0 = v(1). In addition the initial condition is v(0, x) = n 3x/2, 3 − 3x, o 0 < x < 2/3, . 2/3 < x < 1. The solution of the original problem may then be written as u(t, x) = v(t, x) + x. The function v(t, x) may be represented as v(t, x) = ∞ X 2 An e−n π2 t sin(nπx), n=1 where An = 2 Z 1 v(0, x) sin(nπx) dx. 0 Given the piecewise definition of v(0, x) we compute αn = 2 Z 0 2/3 3x sin(nπx) dx = 3 2 Z 2/3 x sin(nπx) dx 0 Z 2/3 cos(nπx) − cos(nπx) 2/3 = 3x dx +3 nπ nπ 0 0 3 cos(2nπ/3) sin(nπx) 2/3 sin(2nπ/3) cos(2nπ/3) = −2 +3 + 3 = −2 nπ n2 π 2 0 nπ n2 π 2 The second piece is βn = 2 Z 1 (3 − 3x) sin(nπx) dx = 6 Z 1 Z 1 (1 − x) sin(nπx) dx 2/3 2/3 cos(nπx) 1 = −6(1 − x) −6 nπ 2/3 =2 2/3 cos(nπx) dx nπ cos(2nπ/3) sin(2nπ/3) dx +6 nπ n2 π 2 Finally, An = αn + βn = −2 cos(2nπ/3) sin(2nπ/3) sin(2nπ/3) cos(2nπ/3) + 2 +3 + 6 nπ n2 π 2 nπ n2 π 2 =9 sin(2nπ/3) . n2 π 2 9. Solve utt = c2 uxx for 0 < x < π with the boundary conditions ux (t, 0) = ux (t, π) = 0, and the initial conditions u(0, x) = 0, ut (0, x) = cos2 (x). Solution The general solution has the form (see p. 89 (7)) ∞ A0 B0 t X u(t, x) = + + [An cos(nct) + Bn sin(nct)] cos(nx). 2 2 n=1 Since u(0, x) = 0, we have coefficients An = 0 for all n. Use the trig identity cos2 (x) = 1 1 + cos(2x). 2 2 Now equate both forms of the initial condition ∞ 1 1 B0 X ut (0, x) = + cos(2x) = + ncBn cos(nx). 2 2 2 n=1 4 We find that B0 = 1, B2 = 1 . 4c Otherwise Bn = 0. Thus u(t, x) = 1 t + sin(2ct) cos(2x). 2 4c Text section 5.2 3. Prove that even functions f (x) and odd functions g(x) satisfy Z l g(x) dx = 0, −l Z l f (x) dx = 2 l Z f (x) dx = 0. 0 −l Solution By definition an even function satisfies f (x) = f (−x) while an odd function satisfies g(−x) = −g(x). For an odd function g(x), Z l g(x) dx = = 0 g(x) dx + l g(−t) dt + 0 Z l Z g(x) dx 0 −l −l Z Z l g(x) dx == Z l (−g(x) + g(x)) dx = 0. 0 0 Here we made a substitution t = −x in the integral. For an even function f (x), Z l f (x) dx = = l f (−t) dt + 0 0 f (x) dx + Z l f (x) dx = 0 Z Z l f (x) dx 0 −l −l Z Z l (f (x) + f (x)) dx = 2 0 Z l f (x) dx. 0 4. a) Use property (5) to prove that if φ(x) is an odd function, then its full Fourier series on (−l, l) has only sine terms. Solution The Fourier cosine coefficients are Z 1 l An = f (x) cos(nπx/l) dx. l −l 5 Since cos(nπx/l) is even and the product of an even function and an odd function is odd, the integrand is odd. Thus An = 0 for all n. b) Also, if φ(x) is even, then its full Fourier series on (−l, l) has only cosine terms. Solution The Fourier sine coefficients are 1 Bn = l Z l f (x) sin(nπx/l) dx. −l Since sin(nπx/l) is odd and the product of an even function and an odd function is odd, the integrand is odd. Thus Bn = 0 for all n. 7. Show how the full Fourier series on (−l, l) can be derived from the full series on (−π, π) by changing variables x′ = πx/l. Solution Suppose we have a function f (x) defined on (−l, l) whose Fourier coefficients are desired. Assume we know the Fourier coefficients A′n and Bn′ of g(x′ ) = f (lx′ /π) for −π < x′ < π. Then making the indicated substitution we have 1 An = l 1 = l Z Z l f (x) cos(nπx/l) dx −l π 1 f (lx /π) cos(nx )l/π dx = π −π ′ ′ ′ 6 Z π g(x′ ) cos(nx′ ) dx′ = A′n . −π